Pengaruh Motivasi, Kompetensi Pedagogik dan Model Project Based Learning terhadap Hasil Belajar Siswa - Sopan Sopari; Siti Fatchia Roesida; Rizkya Amelia (CV. Syntax Corporation Indonesia, 2022)
Vocational secondary education is education that prioritizes the development of students' abilities for certain types of work or vocational secondary education is focused on skills to improve the competence of students so that they can live independently and participate in further education in accordance with their profession. The purpose of this study was to determine the significant effect of motivation, pedagogic competence and project based learning models on student learning outcomes. The sample used was 83 class XII students of SMK Insan Mulya with the research method used descriptive quantitative methods through questionnaire research instruments, literature and direct survey research at the research site of SMK Insan Mulya. The results of the research prerequisite test show that all the variable instruments meet the requirements and deserve to be tested, and based on the results of the study it can be concluded that there is a significant influence between motivation, pedagogic competence and project based learning on learning outcomes. 5%, the contribution of pedagogic competence is 79.2% and the contribution of project based learning is 43%. It can be concluded that pedagogic competence and project based learning greatly affect student learning outcomes. Researchers suggest that students are able to motivate themselves and get used to independent learning by seeking knowledge of productive subjects from various sources of information, not only relying on knowledge in school.